Fabrication and study of sol-gel ZnO films for use in Si-based heterojunction photovoltaic devices - Daniya Mukhamedshina; Konstantin Mit’; Nikolay Chuchvaga; Nurlan Tokmoldin (Modern Electronic Materials, 2017)
This paper considers the use of zinc oxide thin films prepared via the sol-gel route as an n-type layer in heterojunction ZnO/Si solar cells. The ZnO films were prepared via a simple spin-coating technique using zinc acetate dihydrate as a zinc precursor, isopropanol as a solvent and monoethanolamine as a stabilizing agent. Optical, structural and morphological properties of ZnO were investigated for thin films grown from sol-gel solutions with different concentrations both on glass and silicon substrates. As such, a distribution of crystallite sizes and surface topology parameters corresponding to various zinc acetate dihydrate concentrations were obtained to elucidate optimal film deposition conditions. Correlation between thin film morphology and structural characteristics of ZnO thin films was made based on atomic-force microscopy studies. Finally, our results on fabrication, characterization and simulation of ZnO/Si heterojunctions for use as photovoltaic devices are presented. Although noticeable rectifying and photovoltaic properties were observed for Al/Si/ZnO/Ti/Au devices, there appears to exist a considerable room for device improvement with simulation studies suggesting that efficiencies of the order of 24% may be obtained for devices with optimal silicon wafer passivation, i.e. with lifetimes of the order of 1000 μs.